CONSTRUÇÃO DE UM FORNO BASCULANTE PARA FUNDIR LIGAS NÃO FERROSAS - HEIMBURG, EDUARDO M. V.; GILAPA, GENARO M. M.; CARPES, JONATAS V.; HEIMBURG, JULIO C. V.; EGEWARTH, MOZART B. (Salão do Conhecimento, 2013)
Resumo